2017
DOI: 10.3389/fbuil.2017.00020
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Static Pressure and Duration Effects on Tornado-Induced Peak Pressures on a Low-Rise Building

Abstract: This study investigated the role of duration and tornado-induced static pressure on peak pressures on a low-rise building. A tornado simulator was used to generate both translating and stationary vortices to measure pressure time series on a building model. Time-resolved velocity measurements were also made on the vortex to aid in the analysis. Past studies have suggested that peak pressures on buildings in tornadoes were up to 50% higher than straight-line atmospheric boundary layer values as provided by ASCE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Haan et al (2010) using a laboratory tornado simulator and a single gable building model with no openings, reported that vertical and lateral tornado-induced wind loads exceeded ASCE 7 wind loads by factors as high as 3 and 1.6, respectively, when atmospheric pressure was included. Haan (2017) using the same experimental data from Haan et al (2010), subsequently found that analytically removing the atmospheric pressure component brought tornado-induced wind loads closer to ASCE 7 wind loads, but the aerodynamic loading still differed significantly from that expected under straight-line winds, with local tornadoinduced wind pressures in some zones exceeding ASCE 7 pressures by as much as 89%. Yousef and Panneer Selvam (2018) compared wind pressures in tornado-like winds against those generated in straight-line winds on dome-shaped and prismatic buildings using large eddy simulation, finding that tornado forces exceeded the straight-line wind induced forces by factors of 1.5 laterally and 1.3 vertically, with tornado-induced wind pressures greater by factors as high as 2.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Haan et al (2010) using a laboratory tornado simulator and a single gable building model with no openings, reported that vertical and lateral tornado-induced wind loads exceeded ASCE 7 wind loads by factors as high as 3 and 1.6, respectively, when atmospheric pressure was included. Haan (2017) using the same experimental data from Haan et al (2010), subsequently found that analytically removing the atmospheric pressure component brought tornado-induced wind loads closer to ASCE 7 wind loads, but the aerodynamic loading still differed significantly from that expected under straight-line winds, with local tornadoinduced wind pressures in some zones exceeding ASCE 7 pressures by as much as 89%. Yousef and Panneer Selvam (2018) compared wind pressures in tornado-like winds against those generated in straight-line winds on dome-shaped and prismatic buildings using large eddy simulation, finding that tornado forces exceeded the straight-line wind induced forces by factors of 1.5 laterally and 1.3 vertically, with tornado-induced wind pressures greater by factors as high as 2.…”
Section: Introductionmentioning
confidence: 83%
“…For example, the choice of reference velocity for tornadoes, the choice of gust factor for re-referencing the TPU pressure coefficients, and other experimental or analysis choices can contribute to the differences observed. But more importantly, the mechanics of tornado-induced wind loads, with significant vertical velocity components, accelerating flow, and more are fundamentally different than what is simulated by boundary layer wind tunnels, as evidenced in several recent studies (Haan, 2017;Kopp and Wu, 2017). As of yet however, it is unclear to what extent each of these factors contribute to potential differences in observed wind loads.…”
Section: Conclusion and Discussionmentioning
confidence: 99%